What factors influence the mobile health service adoption? A meta-analysis and the moderating role of age. (December 2018) - Zhao, Yang; Ni, Qi; Zhou, Ruoxin
Abstract: As an emerging field in the healthcare industry, mobile health service has been paid more and more attention in recent years. To explore the key determinants of individual attitude and behavioral intention, this study, based on 35 related empirical researches, conducted a meta-analysis to develop a comprehensive framework regarding the adoption of individual mobile health services and analyzed the moderating effect of age. Through descriptive statistics, reliability statistics, and correlation analysis, the results of meta-analysis indicate that perceived usefulness, perceived ease of use, perceived vulnerability and perceived severity all have significant impacts on individual attitude, while perceived usefulness, perceived ease of use, subjective norm, trust, perceived risk and attitude significantly influence behavioral intention. The moderator analysis confirmed that different age groups have specific moderating effects on mobile health services adoption, and results suggest that perceived ease of use, perceived vulnerability and perceived severity are more important factors for middle-aged and older users to use mobile health services.